Chirped periodic waves for an cubic-quintic nonlinear Schrödinger equation with self steepening and higher order nonlinearities. (March 2022) - Seadawy, Aly R.; Rizvi, Syed T.R.; Mustafa, B.; Ali, K.; Althubiti, Saeed
Abstract: In this paper, we study the cubic-quintic nonlinear Schrödinger equation (CQ-NLSE) to describe the propagation properties of nonlinear periodic waves (PW) in an optical fiber. We find chirped periodic waves (CPW) with some Jacobi elliptic functions (JEF). We also obtain some solitary waves (SW) like dark, bright, hyperbolic and singular solitons. The chirp that corresponds to each of these optical solitons is also determined. The pair intensity is shown to be related to the nonlinear chirp, which is determined by self-frequency shift and pause self-steepening (SS). The shape of profile for these waves will also be display.